The effects of high-intensity interval training in well-trained rowers - Driller, M. W.; Fell, J. W.; Gregory, J. R.; Shing, C. M.; Williams, A. D. (International Journal of Sports Physiology and Performance, 2009)
Purpose: Several recent studies have reported substantial performance and physiological gains in well-trained endurance runners, swimmers, and cyclists following a period of high-intensity interval training (HIT). The aim of the current study was to compare traditional rowing training (CT) to HIT in well-trained rowers. Methods: Subjects included 5 male and 5 female rowers (mean ± SD; age = 19 ± 2 y; height = 176 ± 8 cm; mass = 73.7 ± 9.8 kg; VO2peak = 4.37 ± 1.08 L/min). Baseline testing included a 2000-m time trial and a maximal exercise test to determine VO2peak, 4-min all-out power, and 4 mmol/L blood lactate threshold. Following baseline testing, rowers were randomly allocated to HIT or CT, which they performed seven times over a 4-wk period. The HIT involved 8 x 2.5-min intervals at 90% of the velocity maintained at VO2peak, with individual recoveries returning to 70% of the subjects` maximal heart rate between intervals. The CT intensity consisted of workloads corresponding to 2 and 3 mmol/L blood lactate concentrations. On completion of HIT or CT, rowers repeated the testing performed at baseline and were then allocated to the alternative training program and completed a crossover trial. Results: HIT produced greater improvements in 2000-m time (1.9 ± 0.9%; mean ± SD), 2000-m power (5.8 ± 3.0%), and relative VO2peak (7.0 ± 6.4%) than CT. Conclusion: Four weeks of HIT improves 2000-m time-trial performance and relative VO2peak in competitive rowers, more than a traditional approach.